LG CNS Digital Transformation Using Robotic Process Automation - Lee, Jung Ho; Lim, Eunyoung; Chung, Namho (Business Communication Research and Practice, 2022)
Objectives: Robotic process automation (RPA) has emerged as a trend in various industries due to the increasing interest in digital transformation and innovations. RPA has been actively applied in the financial and service industries, and the ability to integrate artificial intelligence (AI) technology has prompted firms in many industries to adopt RPA to increase the efficiency of their business operations. This study aims to find out how companies adopt RPA based on LG CNS' RPA application cases. Methods: The method of collective case studies with multiple case was used. To this end, this study analyzed and organized multiple cases exemplifying the applications of RPA in LG CNS for various purposes, such as the verification of outside information from an unassociated system, simple information verification, system input tasks, and data reconciliation. Results: Several considerations should be kept in mind for the functional implementation of AI-based RPA. Research is needed on the characteristics of specific types of applications, and an optimized RPA solution requires careful consideration of which processes will be automated by AI and how best to do so. Conclusions: RPA automates simple repetitive tasks, standardizing business processes and helping to increase the efficiency of administrative processes. Therefore, RPA should be validated for use in administrative tasks at public institutions. However, there are limits and points to consider from the standpoint of application processes, legislative issues, and governance. For these reasons, there is a need for more research and case studies on RPA technology and related industries before it can be deployed more widely. KCI Citation Count: 2